Uzņēmējdarbības vadītāja profesionālās kompetences pilnveidošana Latvijā - Kulberga, Inta (Latvijas Universitāte, 2013)
Promocijas darba mērķis: analizēt uzņēmējdarbības vadītāja profesionālās kompetences struktūras izmaiņu saturu mūsdienu mainīgā vidē, un, pamatojoties uz teorētisko un empīrisko pētījumu rezultātiem, izstrādāt uzņēmējdarbības vadītāja profesionālās kompetences pilnveidošanās modeli Latvijā. Pirmajā nodaļā raksturota saimniekošanas pārmaiņu ietekme XXI gadsimta uznņēmumu vadīšana un vadītāja loma mūsdienu uzņēmumos. Otrajā nodaļā konkretizēts uzņējdarbības vadītāja profesionālās kompetences jēdziens, tās struktūras sastāvs, raksturots vadītāja kompetenču modelis. Trešajā nodaļā veikta empīrisko pētījumu rezultātu par uzņēmējdarbības vadītāja profesionālās kompetences pilnveidošanas nepieciešamību pārmaiņu apstākļos un zināšanu vadīšanu Latvijas uzņēmumos analīze un interpretācija. Ceturtajā nodaļā pētīts profesionālās izglītības produkta jēdziens un uzņēmējdarbības vadītāja kompetences veidošanās Latvijas augstakajā profesionālajā izglītībā. Piektajā nodaļā analizēta uzņēmējdarbības un izglītības institūciju sadarbības sekmēšana Latvijā, izvirzīti izglītības iestāžu jaunie stratēģijas virzieni un zināšanu vadīšanas paņēmieni uzņēmumos. Darba noslēgumā apkopoti secinājumi un izvirzīti priekšlikumi.

The goal of the Doctoral Thesis “Development of Entrepreneurship Manager’s Professional Competence in Latvia” is to analyse the content of structural changes of entrepreneurship manager’s professional competence in the modern changeable environment, and on the basis of the theoretic and empiric research results work out a model for entrepreneurship manager’s professional competence development in Latvia. In the first chapter the influence of management changes in the 21st century business management and the manager’s role in the modern companies have been described. In the second chapter the term of entrepreneurship manager’s professional competence has been specified, its structural content, the model of manager’s competences has been described. In the third chapter the analysis and interpretation of the necessity of the empiric research results about entrepreneurship manager’s professional competence development in the changeable conditions and knowledge management in Latvia companies have been carried out. In the fourth chapter the term of the professional education product and entrepreneurship manager’s competence formation in Latvia higher professional education has been studied. In the fifth chapter the promotion of cooperation in Latvia between the entrepreneurship and educational establishments has been analyzed, the new strategic directions of educational establishments and knowledge management methods of companies have been set. Some conclusions and suggestions are given at the end of the paper. The Doctoral Thesis consists of 167 computer based pages, it includes 10 tables, 42 pictures, and 12 appendices have been added and 158 literature resources. Key words: entrepreneurship manager, professional competence, knowledge management, education product, cooperation.
Elektroniskā versija nesatur pielikumus
Keywords: Vadībzinātne; Uzņēmējdarbības vadītājs; Profesionālā kompetence; Zināšanu vadīšana; Izglītības produkts; Entrepreneurship manager; Professional competence; Knowledge management